Plantas medicinais utilizadas no nordeste brasileiro no tratamento de afecções de vias aéreas: uma revisão de literatura - Rodrigues, Luciana Carla Freitas (Universidade Federal Rural do Semi-Árido, 2020)
The use of medicinal plants in the treatment of diseases is as old as humanity itself. Historical and archaeological evidence that demonstrates, over time, as diverse societies around the world, developing an empirical form or therapeutic knowledge for accompanying diseases, thus building, as bases of traditional medicine. Among the pathologies treated through the use of medicinal plants, it can be highlighted, mainly, as respiratory treatment diseases. In Brazil, as a respiratory condition, it reduces 14% of hospitalizations in the public health system, being a prominent region between the years 2013 to 2017, with more than 1,500.00 hospitalizations for respiratory causes. The objective of this study was to carry out a systematic bibliographic review of the ethnobotanical studies carried out in the Northeast of Brazil between the periods 2010 - 2020, in order to identify as the main medicinal plants used in respiratory tract problems. Scientific articles on the subject were accessed in the scientific databases: PUBMED, SCIELO and LILACS in a period of December 2020. In accordance with the inclusion and exclusion requirements, 9 articles were selected for final analysis. Among the nine articles analyzed, 139 species were found, distributed in 60 different families. In this research, the species that stood out the most was Hymenaea courbaril L. being mentioned 7 times in different studies analyzed. Acanthospermum hispidum DC, Amburana cearenses, Ziziphus joazeiro Mart. were cited 5 times, occupying the second most cited position. The species Allium sativum L received 4 citations, being the third most cited species. The results of the present study demonstrate that the Northeast has a vast flora of medicinal plants and that species, such as Hymenaea courbaril L, Acanthospermum hispidium DC, Amburana cearensis, Ziziphus joazeiro Mart. and Allium Sativum L has proven therapeutic properties, with great potential for use in primary or complementary therapies in the treatment of respiratory diseases and other pathologies.
Keywords: Brasil; Doenças respiratórias; Etnobotânico; Fitoterapia; Plantas medicinais; Brazil; Ethnobotanical; Fitoterapy; Phytotherapy; Medicinal plants; Respiratory; CIENCIAS DA SAUDE::MEDICINA